1996
DOI: 10.1063/1.871989
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the dynamo effect in a plasma

Abstract: A series of detailed experiments has been conducted in three laboratory plasma devices to measure the dynamo electric field along the equilibrium field line ͑the ␣ effect͒ arising from the correlation between the fluctuating flow velocity and magnetic field. The fluctuating flow velocity is obtained from probe measurement of the fluctuating E؋B drift and electron diamagnetic drift. The three major findings are the following: ͑1͒ The ␣ effect accounts for the dynamo current generation, even in the time dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 29 publications
3
45
0
Order By: Relevance
“…In the low density plasmas, the MHD dynamo dominates while at the highest density, the diamagnetic dynamo dominates. Although the underlying mechanisms for the transition are still unclear, this observation is consistent [26] with the early measurements in a dense plasma where no significant MHD dynamo was detected [18].…”
Section: Diamagnetic Dynamosupporting
confidence: 78%
“…In the low density plasmas, the MHD dynamo dominates while at the highest density, the diamagnetic dynamo dominates. Although the underlying mechanisms for the transition are still unclear, this observation is consistent [26] with the early measurements in a dense plasma where no significant MHD dynamo was detected [18].…”
Section: Diamagnetic Dynamosupporting
confidence: 78%
“…The agreement is striking, and confirms earlier measurements with a complex Langmuir probe. 7 However, the same measurement made deeper into the plasma, around the q = 0 surface at r/a ≈ 0.80, do not exhibit the same agreement with simple Ohm's law modeling. The cause of this disagreement is currently unknown; it may be an instrumental artifact resulting from perturbation of the plasma as the probe is inserted more deeply, or it may be that terms other than v ˜ H B ˜ are required to balance Ohm's law.…”
Section: A Previous Workmentioning
confidence: 70%
“…Not all liquid-metal experiments have had such results: Frick et al have reported [13] that the mean flow accounts for all magnetic fields in their torus-shaped gallium experiment, and Peffley, Cawthorne and Lathrop [14] have observed no such effects. It should also be noted that an α-effect has been observed in the core of magnetically-confined plasmas [15,16].In this Letter we report measurements of the magnetic field induced by applying an axisymmetric magnetic field to a turbulent, axisymmetric flow of liquid sodium. An induced dipole moment is measured which cannot be generated by the mean flow, indicating the presence of a turbulent EMF.…”
mentioning
confidence: 96%
“…Not all liquid-metal experiments have had such results: Frick et al have reported [13] that the mean flow accounts for all magnetic fields in their torus-shaped gallium experiment, and Peffley, Cawthorne and Lathrop [14] have observed no such effects. It should also be noted that an α-effect has been observed in the core of magnetically-confined plasmas [15,16].…”
mentioning
confidence: 99%